The impact of corporate taxes on investment: An explanatory empirical analysis for interested practitioners - Daniel Dreßler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
The scientific literature provides evidence for an impact of company taxes on investments. Practitioners, however, have a skeptical view on the meaning of this effect. This paper builds the bridge between research and the interested practice by providing detailed descriptives and clearly showing how the effects are derived. It analyzes the development of German multinationals' direct investments abroad and of foreign multinationals' investments in Germany from 1996 till 2008. A split along federal states is applied. Starting from the analysis of the basic tax effect, the paper also covers current research topics when analyzing the impact of existing loss carryforwards and when tracing holding structures. The descriptive statistics already show that cross-border investments have increased strongly. The development of Baden-Württemberg mainly corresponds to that of Germany. The impact of taxation on investments is negative. A ten percentage points higher corporate tax rate leads to about five percent lower investments, measured by fixed assets. This effect is smaller for those companies which show loss carryforwards. A lower tax rate at a specific location especially seems to attract holding companies, which are applied for tax efficient group structuring.
Keywords: F23; H25; H32; 330; Corporate Taxation; Foreign Direct Investment; Empirical Analysis; Multinational Firms; Unternehmensbesteuerung; Körperschaftsteuer; Steuerwirkung; Direktinvestition; Ausländisch; Multinationales Unternehmen; Deutsch; Schätzung; Deutschland